SUSTAINABLE CULTIVATION PRACTICES FOR MITIGATION OF CLIMATE CHANGE ON PEPPER (Capsicum annuum L.) CROP - Drvoshanova Biljana; Bandzo Oreshkovikj Katerina; Poposka Hristina (Journal of Agricultural, Food and Environmental Sciences (JAFES), 2023)
This study investigates the potential of integrating sustainable agricultural practices to mitigate climate change impacts on the cultivation of pepper (Capsicum annuum L.) in the arid regions. Climate-induced challenges such as desertification have further aggravated the issue of pepper cultivation. The experiment was executed in Kochani region in 2021, employing a randomized block design with five different fertilizer treatments including a notable biofertilizer, Trichoderma harzianum. The agronomic parameters such as fruit length, diameter, mass, pericarp thickness, and yield have been analysed. The mixed fertilization treatment (MIX) illustrated a significant enhancement in fruit dimensions and yield, whereas the Trichoderma treatment (TRICH) exhibited a notable reduction in non-marketable fruits. The findings validate that the incorporation of Trichoderma with organic and mineral fertilizers not only bolsters plant growth and yield, but also strengthens climate resilience in pepper cultivation. This increases the understanding of biofertilizer utilization in sustainable agriculture, especially in regions struggling with climate adversities. Furthermore, the study underpins the necessity for advanced knowledge in leveraging live organisms like Trichoderma for increasing agricultural productivity and climate resilience in arid regions.
Keywords: Trichoderma, pepper fruit traits, marketable yield